Expression of immunogenic genes of Mycobacterium avium subsp. paratuberculosis - Manesh Kumar, P; Vijayarani, K; Kumanan, K (The Indian Journal of Animal Sciences, 2022)
SUMMARY Johne’s disease is an economically important disease caused by Mycobacterium avium subsp. Paratuberculosis (MAP). Continuous efforts are being made to identify MAP genes with antigenic and immunogenic capabilities which may serve as vaccine candidates and diagnostic antigens. mptD and 35 KDa antigen genes of MAP amplified by Polymerase chain reaction resulted in 630bp and 830 bp products respectively. Both mptD and 35 KDa antigen genes were cloned in to pTZ57R/T cloning vector, and subsequently subcloned into pET22b and expressed in BL21 (DE3) host system. The expressed recombinant antigens could be tested in diagnostic assays and might open up the avenue for the development of newer diagnostics and vaccine candidates for Johne’s disease.